Wiki-based collaborative writing viza-viz face to face instruction - Dr. Befikadu Lemma (Science and Education, 2023)
This study was a quasi-experimental one that looked into the effects about wiki-based platforms for group writing on 39 comparison of the writing abilities of students in an online (wiki) classroom with conventional writing. The participants (section L1; 20 students and section L2; 19 students) were first-year engineering students selected 40 sections. The total numbers of students in each section were 20 and 19 respectively. The students were enrolled in a course for no credit called “Essay Writing” for 6 weeks and were randomly assigned into experimental online/wiki group (section L2) and control conventional writing group (section L). Students in the experimental classroom wrote collaboratively on a wiki; in the control classroom, they conversed face-to-face and wrote on notebooks or papers. By comparing the information gathered from a pretest and posttest of individual writing, both groups were evaluated. Descriptive statistics, such as frequency, mean, and standard deviation, and inferential statistics were used to assess these quantitative data (paired samples t-test and independent samples t-test). There are statistically significant changes in the experimental group’s writing performance, according to the results of the paired samples t-test analysis of each student’s writing on the pretest and posttest. On the other hand, there were no statistically significant differences between the treatment and control groups’ posttest scores for the writers’ usage of language, organization, content and mechanics. As a result, EFL writing skills teachers should integrate collaborative writing through social media into their curricula cautiously.